2016
DOI: 10.1063/1.4961003
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear absorption of short intense laser pulse in multispecies plasma

Abstract: In the present paper, the detailed investigation concerning the effect of inclusion of heavy negative ions into the finite background plasma on the laser absorption has been carried out by employing particle-in-cell simulation method. For this purpose, in this configuration, the laser energy absorption relying on the nonlinear phenomena such as phase-mixing, wave-breaking, and scattering has been studied in the Raman-Brillouin regime. It is shown that the inclusion of heavy negative ions suppresses the scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There are also many phenomena in plasma that are not yet well understood. To gain a better understanding of these phenomena, we need to know the plasma parameters of which density and temperature are the most important parameters to identify it [12,13].…”
Section: Intruductionmentioning
confidence: 99%
“…There are also many phenomena in plasma that are not yet well understood. To gain a better understanding of these phenomena, we need to know the plasma parameters of which density and temperature are the most important parameters to identify it [12,13].…”
Section: Intruductionmentioning
confidence: 99%
“…With an intensity greater than 10 18 W cm −2 , the laser pulse creates a pressure of about 10 3 Mbar in underdense plasma and heats the plasma electrons [22]. Particle-in-cell (PIC) simulations depict rigorous laser absorption in finitesize multispecies plasmas and promise the enhancement in the Raman-Brillouin scattering process [23]. In an atmospheric medium, homonuclear molecules, such as O 2 and N 2 are abundant.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption of high-power lasers in plasmas has been an interesting topic for research over the past several years because it offers very promising applications such as fast and shock ignition scenarios in inertial confinement fusion [1,2], plasma heating [3], high-energy beam production [4], plasmabased particle acceleration [5,6], and phenomenological astrophysics [7]. The nonlinear laser energy absorption process in an underdense plasma is considerably supported by converting the laser energy into high-gradient plasma wakefields damped in the plasma through nonlinear effects [8]. In this scenario, the wave-breaking phenomenon occurs for the excited highamplitude plasma wave which causes the excited wave to be nonperiodic, resulting in plasma particle energization by the plasma wave [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that in a finite-size plasma backward scattering increases in the presence of an external magnetic field, resulting in the reduction of laser absorption in the environment [18]. This effect can be modified by adding heavy negative ions into the plasma to suppress the scattering process [8]. Furthermore, the role of parametric instabilities in the absorption of high-power lasers in magnetized plasmas [19] as well as in pair-ion plasmas [20] has been previously reported using one-dimensional (PIC) simulation.…”
Section: Introductionmentioning
confidence: 99%